2015
DOI: 10.1073/pnas.1418603112
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matrix-associated protein SMAR1 regulates alternative splicing via HDAC6-mediated deacetylation of Sam68

Abstract: Pre-mRNA splicing is a complex regulatory nexus modulated by various trans-factors and their posttranslational modifications to create a dynamic transcriptome through alternative splicing. Signalinduced phosphorylation and dephosphorylation of trans-factors are known to regulate alternative splicing. However, the role of other posttranslational modifications, such as deacetylation/acetylation, methylation, and ubiquitination, that could modulate alternative splicing in either a signal-dependent or -independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…30 In addition, the variant exon inclusion of CD44 was regulated by BTG3associated nuclear protein via histone deacetylase 6 mediated deacetylation of KHDRBS1. 31 Our analysis could provide numerous prognostic AS events that may play a critical role in KIRC. For example, Polybromo 1 (PBRM1) was found to be the second most mutated in KIRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, the variant exon inclusion of CD44 was regulated by BTG3associated nuclear protein via histone deacetylase 6 mediated deacetylation of KHDRBS1. 31 Our analysis could provide numerous prognostic AS events that may play a critical role in KIRC. For example, Polybromo 1 (PBRM1) was found to be the second most mutated in KIRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further investigations are warranted to examine the effect of HDAC inhibitors on the target drug sensitivity of tumors with BIM SNPs. HDACs can affect alternative mRNA splicing (24)(25)(26). For instance, the Hu proteins are thought to regulate pre-mRNA splicing through HDAC2 inhibition, which in turn modulates chromatin structures to alter splicing of NF1 in HeLa cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the acetylation of Sam68 is suggested to enhance its activities of RNA binding and splicing regulation in breast and prostate cancers. It is indicated that an acetyltransferase CBP could regulate Sam68 acetylation [110], while histone deacetylase 6 (HDAC6) causes Sam68 deacetylation in cooperation with a nuclear matrix-associated protein, scaffold/matrix-associated region-binding protein 1 (SMAR1), in breast cancer [111]. With respect to HDAC6, it is suggested that HDAC6 interacts with ERα in an ER ligand-dependent manner and subsequently upregulates deacetylation of α-tubulin in breast cancer cells [112].…”
Section: Src Associated In Mitosis Of 68 Kda (Sam68)mentioning
confidence: 99%